Aromaterapi Bitter Orange - Ulya, Yadul; Maya Herlina, Siskha; Suryati Pratiwi, Yopi (STIKES Yarsi Mataram, 2021)
Labor is a series of physiological and psychological processes that can cause labor pain, anxiety and fatigue. One of the non-pharmacological therapies to reduce labor pain is aromatherapy. Aromatherapy is a non-pharmacological therapy that uses pure essential oils. Aromatherapy Bitter Orange is a non-pharmacological therapy to reduce or relieve pain in mothers who give birth during the first period.Citrus Aurantium or better known as Bitter Orange (bitter orange) contains limonene, linalool, linalyl acetate, geranyl acetate, geraniol, nerol, and neryl acetate. This oil has a reactive, anti-septic, anti-spasmodic and mild sedative effect. Limonele found in bitter orange (Citrus Aurantium) oil controls cyclooxygenase I and II, prevents prostaglandin activity and reduces pain. Based on several studies, it can be concluded that bitter orange (Citrus Aurantium) aromatherapy can reduce labor pain during the 1st stage of the active phase.